Review of the genus Pteranabropsis Gorochov, 1988 (Orthoptera: Anostostomatidae: Anabropsinae) with description of two new species from China - Song, Qiong; Guo, Huifang; Bian, Xun; Shi, Fuming (Zootaxa, 2016)
This paper describes two new species of the genus Pteranabropsis Gorochov, 1988 (Orthoptera: Anostostomatidae: Anabropsinae) from China, i.e. Pteranabropsis crenatis Song, Bian & Shi sp. nov. and Pteranabropsis incisa Song, Bian & Shi sp. nov. Meanwhile, the photos of important morphological features and a distribution map of the genus Pteranabropsis Gorochov, 1988 are provided. Also, a key to the species of Pteranabropsis is provided. The examined specimens are deposited in the Museum of Hebei University.